Analisis Kritis Buku Teks Cerdas Cergas untuk Pembelajaran Bahasa Indonesia - Firmansyah, Arif; Marlina, Siska (Universitas Muhammadiyah Surabaya, 2025)
This study aims to analyze the feasibility of the “Cerdas Cergas” textbook in supporting Indonesian language learning based on the Merdeka Curriculum. Through in-depth analysis of the suitability of the material with learning outcomes and linguistic quality, this study found that the “Cerdas Cergas” textbook has good potential in developing students' various language skills. However, there are several aspects that need to be improved, such as using simpler language, providing more diverse examples, and stronger integration with the context of students' lives. The results of this study provide important implications for the development of Indonesian language textbooks in the future, namely the need for textbooks that not only present complete material, but are also able to stimulate students' interest in learning and develop the competencies needed in the 21st century.